Analysis of Religious Conflict in the Film the Imam and the Pastor Using Johan Galtung's Theory of Violence and Conflict Theory - Dena Agustina; Saona Saona (Edunity Kajian Ilmu Sosial dan Pendidikan, 2025)
The purpose of this research is to discuss how conflict and violence occurred in Nigeria in the film The Imam And The Pastor. This research method uses a type of qualitative research through literature study and film analysis. The results and discussion of this study include violence that occurs in Nigerian conflicts, conflicts that occur in Nigeria, and conflict transformations carried out. The conclusion of this study is that the conflict that occurred in Negiria as told in the film The Imam And The Pastor was caused by a lack of mutual respect and was also motivated by the economic downturn at that time. So because of this, violence arises, namely by killing one group with another. This study recommends the importance of a high tolerance attitude between religious people